Quest for Efficacious Next-Generation Taxoid Anticancer Agents and Their Tumor-Targeted Delivery - Ojima, Iwao (J Nat Prod, 2018)
[Image: see text] Paclitaxel and docetaxel are among the most widely used chemotherapeutic drugs against various types of cancer. However, these drugs cause undesirable side effects as well as drug resistance. Therefore, it is essential to develop next-generation taxoid anticancer agents with better pharmacological properties and improved activity especially against drug-resistant and metastatic cancers. The SAR studies by the authors have led to the development of numerous highly potent novel second- and third-generation taxoids with systematic modifications at the C-2, C-10, and C-3′ positions. The third-generation taxoids showed virtually no difference in potency against drug-resistant and drug-sensitive cell lines. Some of the next-generation taxoids also exhibited excellent potency against cancer stem cells. This account summarizes concisely investigations into taxoids over 25 years based on a strong quest for the discovery and development of efficacious next-generation taxoids. Discussed herein are SAR studies on different types of taxoids, a common pharmacophore proposal for microtubule-stabilizing anticancer agents and its interesting history, the identification of the paclitaxel binding site and its bioactive conformation, characteristics of the next-generation taxoids in cancer cell biology, including new aspects of their mechanism of action, and the highly efficacious tumor-targeted drug delivery of potent next-generation taxoids.